Pattern of Parental Handling in Children with Emotional and Behavioural Disorders - A Cross Sectional Study - Gopalan, Dr Mohan Roy G; Dr Rajani Raju (International Journal of Medical Research and Review, 2023)
Abstract The role of biological and social parents in shaping the mental and physical health of a child has been well-documented. Researchers over the years have developed typologies that categorize parental behaviour into prototypes and also examined their influence on the developmental outcome. Parenting styles are often considered a characteristic of the parent which is independent of the characteristics of the developing child while parenting behaviour is considered bidirectional and influenced by early childhood or infant behaviour. An overwhelming body of evidence indicates the close relationship between parenting and childhood behaviour, as well as on the effect of various modifying factors including physiology, parental mental health, cultural differences, ethinicity, and societal factors. Cross-cultural studies in the field have so far been limited largely to developed countries even as the subject is highly relevant to developing economies with their over-stretched mental healthcare systems. The objectives of this study is to determine patterns of parental handling in children with emotional and behavioural disorders consulting the child & adolescent psychiatry clinic in a tertiary care centre, and to determine the correlation of parental handling patterns to the child’s behavioural and emotional symptoms. The present study endeavours to determine the parenting pattern among parents of children utilizing psychiatric services at a tertiary care centre in Kerala, South India.